2000
DOI: 10.1007/s002770050591
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent idiopathic iridocyclitis after autologous peripheral blood stem-cell transplantation followed by G-CSF administration for acute lymphoblastic leukemia

Abstract: We describe a patient who experienced a recurrence of idiopathic iridocyclitis on day 12 after autologous peripheral blood stem-cell transplantation (auto-PBSCT) followed by G-CSF administration for acute lymphoblastic leukemia (ALL). Autologous SCT has been reported to be effective and safe in achieving dose intensification of chemotherapeutic drugs for the treatment of hematopoietic malignancies, but its therapeutic effect on autoimmune diseases is not definite. The findings from the present case suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…27,28 Administration of G-CSF to patients can induce or exacerbate preexisting inflammatory conditions, including uveitis. 29,30 We have previously reported that G-CSFedeficient mice are resistant to collagen-induced arthritis. 31 Wild-type (WT) mice treated with antieG-CSF also had reduced collagen-induced arthritis, even when antieG-CSF was administered therapeutically.…”
mentioning
confidence: 99%
“…27,28 Administration of G-CSF to patients can induce or exacerbate preexisting inflammatory conditions, including uveitis. 29,30 We have previously reported that G-CSFedeficient mice are resistant to collagen-induced arthritis. 31 Wild-type (WT) mice treated with antieG-CSF also had reduced collagen-induced arthritis, even when antieG-CSF was administered therapeutically.…”
mentioning
confidence: 99%
“…Noninfectious inflammatory eye diseases (uveitis, iritis, iridocyclitis, chorioretinitis, scleritis, conjunctivitis) can occur as an isolated manifestation of an autoimmune disease in association with systemic diseases (eg, arthritis, connective tissue diseases, Behçet disease), as a result of a trauma, or as a side effect of medications. HSC donation is generally not recommended during an acute inflammatory process because uveitis has been reported as an adverse event after G-CSF administration [42,43]. In the presence of systemic disease suitability has to be assessed accordingly.…”
Section: Eligibility Criteria In Noninfectious Eye Diseasesmentioning
confidence: 99%
“…Few reports exist about HIV negative immunodepressed individuals who suffered from immune recovery uveitis [1]. IRU occurred in these eyes after tapering of chemotherapy for non-Hodgkin's lymphoma, renal transplantation or even after administration of granulocyte colony stimulating factor [2,3]. Kuo et al reported the largest case series of IRU in 18 individuals with CMV retinitis outside the HIV setting [4].…”
mentioning
confidence: 99%